STING1 in Different Organelles: Location Dictates Function - Zhang, Ruoxi; Kang, Rui; Tang, Daolin (Frontiers in Immunology, 2022)
Stimulator of interferon response CGAMP interactor 1 (STING1), also known as TMEM173, is an immune adaptor protein that governs signal crosstalk that is implicated in many physiological and pathological processes. Although it has been established that STING1 traffics from the endoplasmic reticulum (ER) to Golgi apparatus (Golgi) upon DNA-triggered activation, emerging evidence reveals that STING1 can be transported to different organelles, which dictates its immune-dependent (e.g., the production of type I interferons and pro-inflammatory cytokines) and -independent (e.g., the activation of autophagy and cell death) functions. In this brief review, we outline the roles of STING1 in different organelles (including the ER, ER-Golgi intermediate compartment, Golgi, mitochondria, endosomes, lysosomes, and nucleus) and discuss the potential relevance of these roles to diseases and pharmacological interventions.